2001
DOI: 10.1021/jf010136w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ligand-Specific Phage-Display ScFv against the Herbicide Picloram by Direct Cloning from Hyperimmunized Mouse

Abstract: Immunoglobulin genes were directly isolated from the splenocytes of a BALB/C mouse hyperimmunized with the auxinic herbicide picloram conjugated to bovine serum albumin. Variable light and heavy domain DNA were joined to produce single-chain Fv (scFv) DNA, which was cloned into phage vector fd-tet-GIIID to display multiple copies of scFv on the filamentous phage minor coat protein gIIIp. The phage-display scFv library (10(4) clones) was selected against picloram conjugated to ovalbumin. After five rounds of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
5
26
0
7
Order By: Relevance
“…When affinities of RAbs and those of their parental MAbs have been compared in the literature, diverse results have been reported. While some authors reported that RAbs showed lower affinity than their parental MAb, others reported a comparable or even higher affinity of RAbs over their counterpart MAbs (Graham et al 1995;Kramer and Hock 2007;Nishi et al 2005;Tout et al 2001). Results obtained in this study and those reported in the literature point out that the binding site structure of scFvs differs somehow from that of their respective parental antibody molecules (MAb).…”
Section: Characterization Of Scfv Recombinant Antibodiessupporting
confidence: 39%
See 1 more Smart Citation
“…When affinities of RAbs and those of their parental MAbs have been compared in the literature, diverse results have been reported. While some authors reported that RAbs showed lower affinity than their parental MAb, others reported a comparable or even higher affinity of RAbs over their counterpart MAbs (Graham et al 1995;Kramer and Hock 2007;Nishi et al 2005;Tout et al 2001). Results obtained in this study and those reported in the literature point out that the binding site structure of scFvs differs somehow from that of their respective parental antibody molecules (MAb).…”
Section: Characterization Of Scfv Recombinant Antibodiessupporting
confidence: 39%
“…In this sense, phage-displayed scFv analysis is a more laborious procedure because a phage rescue step is required. Moreover, the size and complexity of phage-displayed scFv may contribute to unspecific interactions that would mask the specific ones (Mersmann et al 1998;Tout et al 2001). …”
Section: Cloning and Expression Of Scfv And Scfv-piii Rab Fragmentsmentioning
confidence: 99%
“…The assay sensitivity for the scFv antibodies is similar to those scFv obtained by Tout et al (2001) and Kramer (1998) for picloram and atrazine. The authors produced the scFv fragments using direct cloning of variable parts of antibody genes from immunized mice or employed recombinant phage antibody system from RPAS, Pharmacia.…”
Section: Discussionsupporting
confidence: 66%
“…A maioria dos trabalhos envolve a utilização de camundongos, pois esses animais apresentam diversas vantagens sobre os demais, entre elas, as facilidades de obtenção, manutenção e manuseio, a vasta disponibilidade de animais de linhagem pura, destinados a diferentes estudos imunológicos, e a resposta imuno-humoral, cuja evolução é bastante semelhante à do homem 19,53 . Contudo, dependendo do tipo de composto a ser testado, nem sempre o uso de animais de pequeno porte, como camundongos 54,55 e coelhos 55,56 , pode levar a uma imunoresposta com a sensibilidade esperada, o que obriga o pesquisador a mudar de animal. Deste modo, ovelhas, porcos, bois, cavalos e camelos têm sido também utilizados em investigações específicas 53,[57][58][59][60] .…”
Section: Produção Dos Anticorpos (Imunização)unclassified